2018
DOI: 10.1186/s40729-017-0115-1
|View full text |Cite
|
Sign up to set email alerts
|

Postgraduate education in dental implantology in the United Kingdom: a review

Abstract: Background: The qualified dentists in the United Kingdom (UK) are not expected to be competent in practising implant dentistry without further training in the subject and there is now greater emphasis on postgraduate training in Dental Implantology. There are three main education pathways at present, yet their training standards vary significantly. This study aims to identify UK postgraduate academic qualifications and continuing professional development (CPD) courses available in the field of Dental Implantol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Secondly, this setting allows a three-dimensional post-operative examination of the achieved implant positions enabling a direct feedback from the instructors to the participants regarding their accuracy. It therefore provides quality-controlled training which has shown a positive effect on patients’ safety [13]. This kind of three-dimensional radiographic examination might be difficult in a clinical setting with respect to the Radiation Protection Ordinances [21, 22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, this setting allows a three-dimensional post-operative examination of the achieved implant positions enabling a direct feedback from the instructors to the participants regarding their accuracy. It therefore provides quality-controlled training which has shown a positive effect on patients’ safety [13]. This kind of three-dimensional radiographic examination might be difficult in a clinical setting with respect to the Radiation Protection Ordinances [21, 22].…”
Section: Discussionmentioning
confidence: 99%
“…The use of templates enabled the instructors to give students feedback on their achieved accuracy. This feedback might be considered as a kind of quality-controlled training which can be directly related to the patients’ safety [13].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, by performing this examination in an undergraduate laboratory course, it is possible to give the students feedback on their performance in regard to their level of accuracy. This might be a step in the direction of quality-controlled training, which also better ensures patients’ safety [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been assessed that quality-controlled training is correlated to patients’ safety [ 9 ]. Furthermore, Lang et al and Mattheos et al stated that implant dentistry should be a part of the curriculum for dental students [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…in implant dentistry had 'led to a significant improvement in the quality of postgraduate education in dental implantology in the UK' . 1 However, the review also concluded that 'the provision of mentoring for implant placements needs to be standardised' , and…”
Section: Fgdp Marks 15 Years Of Raising Standards In Implant Dentistrymentioning
confidence: 99%